AVALIAÇÃO DO SETOR DE SERVIÇOS NAS REGIÕES FRONTEIRA NOROESTE E NOROESTE COLONIAL DO RIO GRANDE DO SUL - Zamberlan, Luciano; Froemming, Lurdes M. S.; Kuhn, Ivo N.; Sparemberger, Ariosto; Blume, Marcelo; Artus, Francieli (Salão do Conhecimento, 2013)
Resumo